Physically-Deposited Hole Transporters in Perovskite PV: NiOx Improved with Li/Mg Doping - Akalin, Salih Alper; Erol, Mustafa; Uzunbayir, Begum; Oguzlar, Sibel; Yildirim, Serdar; Gokdemir Choi, Fatma Pinar; Gunes, Serap; Yilmazer Menda, Ugur Deneb; Mendes, Manuel J. (WILEY, 2024)
Nickel oxide (NiOx) has received a lot of attention as an inorganic hole transport material (HTM) in perovskite solar cells (PSCs) during the last decade, owing to its high hole mobility, chemical stability, good optical transparency, and suitable energy levels that align with the valance band of the perovskite absorber methylammonium lead iodide (MAPbI(3)). This study explores Li and Mg co-doped NiOx thin films physically-deposited from developed sputtering targets obtained through cold isostatic pressing and sintering. After sputtering, the structural, elemental, morphological, optical, and electrical properties of the layers are investigated by XRD, XPS, SEM, AFM, UV-vis spectrophotometer, and Hall-effect; revealing that crystalline, homogeneous, and smooth films are obtained. In particular, improvements in mobility and conductivity values are observed with Li and Mg doping, which contribute to enhanced PSC performance when used as an HTM layer in the glass-indium tin oxide (ITO)/NiOx-based HTM/MAPbI(3)/phenyl butryic acid methyl ester (PCBM)/bathocuproine (BCP)/Ag architecture. The champion solar cell achieves PCE of 15.52%. In addition, the average values of all samples are boosted, J(SC) (from 13.21 to 15.60 mA cm(-2)) and FF (from 59.32% to 67.7%), relative to pristine HTM, resulting in a pronounced PCE increment of up to 30% with the HTM film sputtered by a single target of co-doped material.
Keywords: hole transport material; lithium/magnesium doping; perovskite solar cells; photovoltaics; sputtered nickel oxide; NICKEL-OXIDE FILMS; SOLAR-CELLS; THIN-FILMS; HIGHLY EFFICIENT; PHOTOVOLTAIC PERFORMANCE; OPTICAL-PROPERTIES; LARGE-AREA; DOPED NIO; STABILITY; LAYER; Materials Science